Youth Unemployment determinants in Developing Countries – Indonesian Evidence - Fathoni, Januar Achmad; Sinaga, Obsatar; Razimi, Mohd Shahril Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The Bureau of Labour Statistics explains that unemployment is people who do not have work to do and has actively looked for work during last month and also available to do work. Moreover, people who are laid off temporarily and are in a waiting list to be called back to work are considered unemployed. The people who do not look for work during the last month are not considered unemployed. Unemployment in Youth contributes significantly to total unemployment and it is more than 50% of the total unemployment. The youth of the society are most susceptible to these trends; these people are hired at the last when companies make new hiring due to their lack of experience, poor communication ability of the workers and higher level of information asymmetry in labour market are the reasons of unemployment. Therefore, unemployment’s cyclical nature leads to the intervention of government in the economy which thus make reduction in unemployment during recessions.